SOME METHODOLOGICAL APPROACHES TO PATRIOTIC NATIONAL EDUCATION, CULTURE AND ARTS WORK AMONG CITIZENS OF MONGOLIA - Ichinnorov Oyun; Jalbajav Nanzad (International Journal of Innovative Technologies in Social Science, 2025)
Mongolian patriotism is a complex idea that is shaped by the country’s history, nomadic roots, and interactions with the global community. It is demonstrated through cultural preservation, artistic endeavors, and a deep sense of national pride, often showcased through traditional practices and customs. This blend of tradition and modernity creates a unique patriotic spirit in Mongolian society. This study explores the complex nature of patriotic ideology among Mongolian citizens and its manifestation through cultural and artistic endeavors. Patriotism in Mongolia is defined as a strong attachment to one’s homeland, influenced by traditional values and historical and contemporary social factors. The research investigates how patriotic education functions as a means of safeguarding national security and cultural heritage in the face of globalization and socio-economic changes. Various strategies for promoting patriotic values are examined, including reforms in governance, education, and financial support systems. The study emphasizes the important roles of families, schools, cultural institutions, media, and the Armed Forces in nurturing patriotic sentiment. It also addresses the challenges posed by market forces, declining morals, and external influences that threaten national identity. The study suggests that effective patriotic education should blend traditional Mongolian values with modern democratic principles, drawing on the country’s unique cultural heritage and nomadic traditions. It concludes that enhancing patriotic ideology requires collaborative efforts across society, guided by strong leadership and a commitment to justice, to safeguard Mongolia’s independence, security, and cultural richness.